(untitled) (Global Journal of Human-Social Science, 2019)
Abstarct-Malaysia’s foreign policy has traditionally focused on Southeast Asia and its friends in the West. West Asia was not a priority in its foreign policy despite the long established historical, social, and religious connection between Malaysia and the region. It was not until April 1965 that Malaysia began to develop closer cooperation with members of the Organisation of the Islamic Conference (OIC). The OIC was established with the fundamental purpose of strengthening the solidarity and cooperation among the 59 Members States. Malaysia values its participation within the OIC as part of its foreign policy strategy with other Muslim countries. During the 2003-2007 period, Turkey, Saudi Arabia, and Malaysia were the three largest Muslim majority economies registering significantly larger growth in trade with OIC member countries than with the rest of the world. This paper examines factors shaping Malaysia-West Asia international relations through the perspective of social capital networking with a focus on establishing an "ummah network" between Malaysia and West Asia.